A STUDY ON THE INDO PAKISTAN RELATION SINCE PARTITION AND HOW OVER THE YEARS THE RELATIONSHIP HAS TAKEN A WORST SHAPE ON THE BASIS OF RELIGION NATIONALISM - Dr.Sumanta Bhattacharya; Dr. Jayanta Kumar Ray; Colonel H R Naidu Gade; Bhavneet Kaur Sachdev (Galaxy International Interdisciplinary Research Journal, 2021)
India and Pakistan have agreed on ceasefire recommitment after the COVID-19 pandemic and there are also trying to resolve issues and start trade relation for economic stability Pakistan after the abolition of Article 370 has reduced trade relation with India and there were constant terrorist attacks which resulted in the death of many civilians .India and Pakistan has fought many ways on Kashmir issue and even India fought a way against Pakistan for the liberation of East Pakistan now known as Bangladesh . Every month there is a terrorist attack happening in Kashmir .Pakistan fund terrorist activities and terrorist groups in India along with provide arms and weapons to the Maoist and the North East insurgency , in fact many blast which have happened in India over the last decade has been sponsored by Pakistan indirectly . Across the border drug trafficking , smuggling and infiltration is common . India’s terrorist groups , Naxalite get support from external forces which has caused a serious threat to the internal security of India . Kashmir has become a terrorist state , However with the abolition of article 370 the situation has turned worst .